Socio Demography and Physical Environment Factors Against the Incidence of Dengue Hemorrhagic Fever in Delta Pawan District, Ketapang Regency (Public Health Perspective Journal, 2021)
Dengue Hemorrhagic Fever is an environmentally-based dangerous disease which is still a world health problem. WHO noted that Indonesia is a country with the highest cases of Dengue Hemorrhagic Fever (DHF) in Southeast Asia (WHO, 2016). In 2019 the cases increased with the number of cases 137.761. West Kalimantan Province is one of the 5th highest provinces out of 34 provinces in Indonesia for 2018. Ketapang Regency is in the first place with the highest number of cases in Delta Pawan District. The purpose of this study was to determine the effect of socio demography and physical environment on the incidence of Dengue Hemorrhagic Fever. This study used a case control design. The research sample was 132 respondents (66 cases and 66 controls) respondents obtained by purposive sampling technique. Data collection techniques by interviewing, questionnaires, and observations. Data analysis using chi-square. The results showed that there was a relationship between income (p = 0.024), ventilation (p = 0.005) and water reservoirs (p = 0.023). There was no relationship between population mobility (p = 0.601) and house distance (p = 0.577) with the incidence of dengue hemorrhagic fever. The conclusion of this study is that the variables associated with the incidence of Dengue Hemorrhagic Fever in the Delta Pawan district of Ketapang regency are income, ventilation and water reservoirs variables. It needs to increase health promotion about the dangers of DHF and the importance of PSN (advocacy, atmosphere building, social support and household empowerment) and improve the performance of jumantik through continuous supervision and facilitation, it is necessary to increase awareness by always closing water reservoirs and using gauze. Through these efforts, it is hoped that there will be an increase in larva free (ABJ) and a decrease in the incidence of Dengue Hemorrhagic Fever (DHF).